Evaluation of the Rationality of Antibiotic Use in Pneumonia Patients Using the Gyssens Method - Agustiana Agustiana; Adryan Fristiohady; Muhammad Arba; Asriullah Jabbar; Nur Illiyyin Akib; Suryani Suryani (Newinera Publisher, 2025)
Pneumonia is one of the leading causes of morbidity and mortality worldwide. The irrational use of antibiotics in pneumonia management can reduce therapeutic effectiveness and increase the risk of antimicrobial resistance. This study aimed to evaluate the rationality of antibiotic use in pneumonia patients at Hospital X using the Gyssens method. This research employed a descriptive observational design with a retrospective approach, utilizing medical record data of adult inpatients diagnosed with pneumonia during the period of January–December 2024. A total of 86 patient records meeting the inclusion criteria were analyzed. Evaluation was conducted using the Gyssens method by comparing the appropriateness of therapy with the Guidelines for the Management of Adult Pneumonia issued by the Indonesian Ministry of Health (Regulation No. 28 of 2021) and the Infectious Diseases Society of America/American Thoracic Society (IDSA/ATS, 2023) guidelines. The results showed that the most frequently used antibiotics were Ceftriaxone (34.88%), Azithromycin (32.56%), and Levofloxacin (32.56%). The most common duration of therapy was five days (53.9%). Based on the Gyssens categories, rational antibiotic use (category 0) was found in 57 cases (66.28%), while the remaining cases were categorized as I (6.98%), IIa (11.63%), IIIa (9.30%), and IIIb (5.81%). These findings indicate that most antibiotic use at Hospital X was rational; however, continuous monitoring and periodic evaluation through the Antimicrobial Resistance Control Program (PPRA) are still necessary to optimize therapeutic effectiveness and prevent antibiotic resistance.